Evolusi dan penciptaan manusia: analisis perbandingan antara pandangan ilmiah barat dan perspektif islam - Aziizah, Puan (Maliki Interdisciplinary Journal, 2025)
The debate surrounding the origin of humans has garnered attention across various disciplines, including anthropology, biology, and theology. Modern science, particularly evolutionary theory, posits that humans evolved from primates through the process of natural selection. Meanwhile, religion—especially Islam—holds that the first human, Prophet Adam, was directly created by God. This tension between scientific and religious perspectives raises fundamental questions about human existence. This paper explores how both approaches need not be contradictory, but can instead be integrated to achieve a more comprehensive understanding. Such integration combines scientific facts about human evolution with the spiritual and moral values found in religion, forming a dialogical framework that complements one another. This approach also highlights the importance of openness in considering multiple viewpoints on human origins, both biological and theological. Thus, integrating science and religion offers a broader insight into the human being—not only as a biological entity, but also as a spiritual and moral one.